2020
DOI: 10.1186/s12866-020-02036-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative microbial risk assessment for waterborne pathogens in a wastewater treatment plant and its receiving surface water body

Abstract: Background Access to safe water for drinking and domestic activities remains a challenge in emerging economies like South Africa, forcing resource-limited communities to use microbiologically polluted river water for personal and household purposes, posing a public health risk. This study quantified bacterial contamination and the potential health hazards that wastewater treatment plant (WWTP) workers and communities may face after exposure to waterborne pathogenic bacteria in a WWTP and its as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 48 publications
1
17
4
1
Order By: Relevance
“…The percentage of the EPEC positive samples were very low in our study (2%) which is in accordance with the study reported by Mbanga et al, 2020 (1.7 %) [30]. Osińska et al [31]. however, reported 65% EPEC from raw and processed wastewater from a WWTP in Poland.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The percentage of the EPEC positive samples were very low in our study (2%) which is in accordance with the study reported by Mbanga et al, 2020 (1.7 %) [30]. Osińska et al [31]. however, reported 65% EPEC from raw and processed wastewater from a WWTP in Poland.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of EAEC in our study was also very low (2%) whereas Mbanga et al, 2020, [30] reported 53.3% prevalence of EAEC in samples taken from WWTP which is even higher than that reported by Osińska et al [31] 28%.…”
Section: Discussioncontrasting
confidence: 68%
“…All reactions included a no-template control consisting of the reaction mixture. The real-time PCR protocol was done according to Mbanga et al (10). The primers, virulence genes, and reference strains used to determine pathotypes are shown in Supplementary Table 1.…”
Section: Bacterial Identificationmentioning
confidence: 99%
“…The trend is attributable to high water demand due to population growth, poor infrastructure to harvest water the resource and manage its demand, as well as the resultant wastewater (Fuhrimann et al 2016;Nyika & Onyari 2019;Oki & Quiocho 2020). The pressure is even more in urban and suburban areas with no wastewater management systems and therefore, the population resort to release raw effluent to freshwater bodies resulting in a bigger pollution problem on such resources (Mbanga et al 2020).…”
Section: Introductionmentioning
confidence: 99%